The prevalence of mild cognitive impairment in type 2 diabetes mellitus patients: a systematic review and meta-analysis - You, Yue; Liu, Zhizhen; Chen, Yannan; Xu, Ying; Qin, Jiawei; Guo, Shuai; Huang, Jia; Tao, Jing (Acta diabetologica, 2021)
Aims Mild Cognitive impairment (MCI) is common in type 2 diabetes mellitus (T2DM) patients. The impaired cognitive function had harmful effect on patients’ diabetic conditions. This study aimed to estimate the prevalence of MCI in T2DM (T2DM-MCI) patients by conducting a systematic review and meta-analysis of observational studies. Methods We carried out a literature search until June 1, 2020, for all observational studies in the following databases: Medline (PubMed), Web of Science, and Embase. Two independent reviewers initially screened the eligible articles. Then, a meta-analysis (random effects model) was conducted to estimate the prevalence of MCI in people with T2DM with STATA 16. Results A total of 1808 articles were first considered after reading title and abstract, 12 of which remained after reviewing the full text. The combined prevalence of MCI in T2DM patients was estimated to be 45.0% (95% CI=36.0, 54.0). There was no significant heterogeneity through meta-regression and sensitivity analysis. Overall, Europe ( n =2, r =36.6%, 95% CI=26.3, 46.9, I 2 =82.3%) had a lower prevalence than Asia ( n =10, r =46.4%, 95% CI=36.2, 56.6, I 2 =98%). The overall prevalence in female patients ( n =14, r =46.9%, 95% CI=34, 59.8, I 2 =98.3%) was higher than that in male patients ( n =14, r =38.8%, 95% CI=27, 50.7, I 2 =98%). Subgroup analysis based on age demonstrated a lower prevalence in patients older than 60 years ( n =9, r =44.3%, 95% CI=33.1, 55.6, I 2 =98.3%) than patients younger than 60 years ( n =3, r =46.4%, 95% CI=33.3, 59.5, I 2 =91.2%). Conclusion Our results demonstrate that the pooled estimated prevalence of mild cognitive impairment in type 2 diabetes mellitus patients is high worldwide, especially in China Asia. Primary care clinicians should pay more attention to the cognitive function of T2DM patients, as mild cognitive impairment is one of the risk factors for Alzheimer's disease.